2004
DOI: 10.4141/a03-071
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trait selection for body weight, egg production and total fat in the Chinese and Synthetic strains of geese

Abstract: , J. W. 2004. Multi-trait selection for body weight, egg production and total fat in the Chinese and Synthetic strains of geese. Can. J. Anim. . The Chinese and Synthetic (assembled from Pilgrim, Chinese and Hungarian) strains raised at the Greenbelt farm of the Centre for Food and Animal Research (formerly Animal Research Centre, and Animal Research Institute) located in Ottawa, Canada, had been subjected to 12 yr of random mating. From 1982 onwards, these two strains were selected for five generations in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Both the Synthetic and Chinese strains had been maintained for 12 yr as randombred populations before this study was initiated. Beginning in 1982, the Chinese and Synthetic strains were selected for multiple traits, which included egg production over a 24-wk laying period, body weight at 16 wk of age and total (abdominal and intestinal) fat, described elsewhere (Shrestha et al 2004). Concurrently, randombred populations of the Chinese and Synthetic strains were maintained, in order to monitor year to year trends that might have occurred among the various traits assessed during the course of selection.…”
Section: Methodsmentioning
confidence: 99%
“…Both the Synthetic and Chinese strains had been maintained for 12 yr as randombred populations before this study was initiated. Beginning in 1982, the Chinese and Synthetic strains were selected for multiple traits, which included egg production over a 24-wk laying period, body weight at 16 wk of age and total (abdominal and intestinal) fat, described elsewhere (Shrestha et al 2004). Concurrently, randombred populations of the Chinese and Synthetic strains were maintained, in order to monitor year to year trends that might have occurred among the various traits assessed during the course of selection.…”
Section: Methodsmentioning
confidence: 99%
“…Fortin et al (1983) reported on these same strains prior to the four generations of selection described previously by Shrestha et al (2004b) that the Chinese strain was lighter than the Synthetic strain at slaughter (5.39 vs. 5.67 kg) and for eviscerated carcass weight (3.28 vs. 3.46 kg) but percentage abdominal fat was about the same (5.19 vs. 5.26%). These findings are in contrast to the present study because the Selected Chinese strain not only weighed more compared with the Selected Synthetic strain, but also produced a heavier carcass with similar percentage of abdominal fat.…”
Section: Discussionmentioning
confidence: 86%
“…Consequently specialized strain crosses with the objective of foie gras production need to be developed. The four generations of multi-trait selection in the Chinese and Synthetic strains increased egg production over a 24-wk laying period (1.3 and 1.1 egg generation -1 , respectively) and increased male and female body weight at 16 wk of age (0.18 and 0.17 kg generation -1 , respectively) for the Selected Chinese strain, and (0.09 and 0.08 kg generation -1 , respectively) for the Selected Synthetic strain, without a significant reduction in total fat (Shrestha et al 2004b). The heavier Embden-sired crosses showed a significantly heavier weight gain in live and carcass traits along with a higher fat content than the Selected Chinese and Synthetic strains.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations